2007
DOI: 10.1016/j.cub.2007.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Facial-Expression and Gaze-Selective Responses in the Monkey Amygdala

Abstract: The social behavior of both human and nonhuman primates relies on specializations for the recognition of individuals, their facial expressions, and their direction of gaze. A broad network of cortical and subcortical structures has been implicated in face processing, yet it is unclear whether co-occurring dimensions of face stimuli, such as expression and direction of gaze, are processed jointly or independently by anatomically and functionally segregated neural structures. Awake macaques were presented with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
213
4
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(251 citation statements)
references
References 46 publications
28
213
4
1
Order By: Relevance
“…However, given the copious amounts of anecdotal evidence from humans, and the more recent empirical studies supporting the uncanny valley effect in humans (2, 3), it seems parsimonious to conclude that monkeys are also experiencing at least some of the same emotions. To support this notion, future experiments could incorporate somatic markers, such as skin conductance responses, pupil dilation, or facial electromyography, to measure the emotional responses of monkeys to the differently rendered faces from monkeys (17)(18)(19)(20). Neurophysiological and neuroimaging approaches could also be illuminating in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…However, given the copious amounts of anecdotal evidence from humans, and the more recent empirical studies supporting the uncanny valley effect in humans (2, 3), it seems parsimonious to conclude that monkeys are also experiencing at least some of the same emotions. To support this notion, future experiments could incorporate somatic markers, such as skin conductance responses, pupil dilation, or facial electromyography, to measure the emotional responses of monkeys to the differently rendered faces from monkeys (17)(18)(19)(20). Neurophysiological and neuroimaging approaches could also be illuminating in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous studies have reported various effects of gaze processing in the human amygdala, including enhanced activity to either direct gaze (Kawashima et al, 1999) or averted gaze (Hadjikhani et al, 2008;Staube et al, 2010) or, as in our study, no differential activity for the two gaze directions with static (Wicker et al, 1998) or dynamic stimuli (Pelphrey et al, 2003b;Pelphrey et al, 2004b). Possible explanations for this inconsistency include a low signal-to-noise ratio, since fMRI of subnuclei of the amygdala in monkeys has shown that gaze specific responses are restricted to the central nucleus and the bed nucleus of the stria terminalis (Hoffman et al, 2007); or alternatively, interactions with other experimental factors such as head direction, task instructions, or All values correspond to the number of subjects who exhibited a structural connection between the seed and the target areas, among all 22 volunteers who were scanned. All values correspond to the number of subjects who exhibited a structural connection between the seed and the target areas, among all 22 volunteers who were scanned.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with amygdala damage fail to recognize fear faces (5), although there is now a consensus that the amygdala is involved in processing many emotions from faces, not just fear (11). Electrophysiological recordings in monkeys have found single neurons that respond not only to faces as such (12,13), but also to face identities, facial expressions, and gaze directions (14,15). Single neurons in the human amygdala discriminate faces from inanimate objects (10).…”
mentioning
confidence: 99%